Foreign experience of real estate mass appraisal - M.I. Bondar; А.A. Kulyk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article examines foreign experience in the formation and functioning of mass assessment systems on the example of individual countries. The sample of countries, on the one hand, includes the United States and Sweden as countries where the mass appraisal system has been successfully functioning for decades, and on the other hand, Lithuania, Slovenia, Belarus and Poland, where the formation of a mass appraisal system began only in the late 20th – early 21st centuries. The article covers a comparative analysis and generalization of key aspects of mass appraisal systems of selected countries such as legislative regulation of mass appraisal, administration of the mass appraisal process in the context of the division of functions and powers between key entities, accounting and analysis of input information on the economic and physical-technical characteristics of real estate objects, the use of appraisal approaches and methods for evaluating certain types of real estate, etc. As the world experience shows, the models and procedures of mass appraisal form the basis of modern value-based systems of real estate taxation, since they allow to effectively solving the problems of simultaneously evaluating a large number of objects in conditions of limited time and financial resources. That is why the results of the mass appraisal are primarily used for tax purposes, in particular, to determine the tax base for real estate tax. In some countries, the results of mass appraisal are additionally used in banking and insurance activities, as well as for the purpose of accounting and taxation of real estate in inheritance or donation, etc. Based on the analysis of foreign experience, the article discusses the problems and prospects of introducing a mass appraisal system in Ukraine, in particular, the emphasis is on the lack of appropriate legislative resolution, low openness and transparency of the real estate market, the inconsistency of existing real estate accounting registers with the information needs of mass appraisal, etc. Further research will be directed in the following directions. Firstly, the study of accounting systems for transactions with real estate and accounting systems for the physical-technical characteristics of real estate, corresponding to the information requests of the mass appraisal. Secondly, research of methods and models, development of mass appraisal procedures in accordance with the peculiarities of the local market using as the example the residential real estate market of one of Kyiv districts.